If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + 2v = -11 Solving -3 + 2v = -11 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2v = -11 + 3 Combine like terms: -3 + 3 = 0 0 + 2v = -11 + 3 2v = -11 + 3 Combine like terms: -11 + 3 = -8 2v = -8 Divide each side by '2'. v = -4 Simplifying v = -4
| 15y+44=135 | | 14-c=-15 | | h-47=31 | | 213=77-v | | 198=157-w | | 40x^2+25x= | | -7+v=-5 | | 4x=250x+21 | | 9x+0.9=45.9 | | 155=49-w | | 1/4q=-3 | | 47=4w-17 | | 69=4w+17 | | 50-2x+8x+5=180 | | 6*x^2-x^3=25.25 | | .5*10+5=7.5 | | 2+2w=14 | | a^2+3a=4 | | -27=x/4-7 | | a/6==108 | | -27=-7x/4 | | ln(x-1)=30 | | 7v-6=-146 | | 2x-15y=5 | | 0=y-6+12y^2 | | -16=5+3 | | 3w+7=-11 | | -17=-n-5 | | 4x(2x+8)-1=5 | | 2x+3(400-x)=1050 | | 6f-12=-4f+6 | | 55=-3d+7 |